Trophic cascades in boreal landscapes: top predator protection on tree seedlings and forest grouse - Lyly, Mari. S. (fi=Turun yliopisto|en=University of Turku|, 2016)
Changes in the abundance of top predators have brought about notable, cascading effects in ecosystems around the world. In this thesis, I examined several potential trophic cascades in boreal ecosystems, and their separate interspecific interactions. The main aim of the thesis was to investigate whether predators in the boreal forests have direct or indirect cascading effects on the lower trophic levels. First, I compared the browsing effects of different mammalian herbivores by excluding varying combinations of voles, hares and cervids from accessing the seedlings of silver birch (Betula pendula), Scots pine (Pinus sylvestris) and Norway spruce (Picea abies). Additionally, I studied the effect of simulated predation risk on vole browsing by using auditory cues of owls. Moving upwards on the trophic levels, I examined the intraguild interactions between the golden eagle (Aquila chrysaetos), and its mesopredator prey, the red fox (Vulpes vulpes) and the pine marten (Martes martes). To look at an entire potential trophic cascade, I further studied the combined impacts of eagles and mesopredators on the black grouse (Tetrao tetrix) and the hazel grouse (Tetrastes bonasia), predicting that the shared forest grouse prey would benefit from eagle presence. From the tree species studied, birch appears to be the most palatable one for the mammalian herbivores. I observed growth reductions in the presences of cervids and low survival associated with hares and voles, which suggests that they all weaken regeneration in birch stands. Furthermore, the simulated owl predation risk appeared to reduce vole browsing on birches in late summer, although the preferred grass forage is then old and less palatable. Browsing by voles and hares had a negative effect on the condition and survival of Scots pine, but in contrast, the impact of mammalian herbivores on spruce was found to be small, at least when more preferred food is available. I observed that the presence of golden eagles had a negative effect on the abundance of adult black grouse but a positive, protective effect on the proportion of juveniles in both black grouse and hazel grouse. Yet, this positive effect was not dependent on the abundance foxes or martens, nor did eagles seem to effectively decrease the abundance of these mesopredators. Conversely, the protection effect on grouse could arise from fear effects and also be mediated by other mesopredators. The results of this thesis provide important new information about trophic interactions in the boreal food webs. They highlight how different groups of mammalian herbivores vary in their effects on the growth and condition of different tree seedlings. Lowered cervid abundances could improve birch regeneration, which indirectly supports the idea that the key predators of cervids could cause cascading effects also in Fennoscandian forests. Owls seem to reduce vole browsing through an intimidation effect, which is a novel result of the cascading effects of owl vocalisation and could even have applications for protecting birch seedlings. In the third cascade examined in this thesis, I found the golden eagle to have a protective effect on the reproducing forest grouse, but it remains unclear through which smaller predators this effect is mediated. Overall, the results of this thesis further support the idea that there are cascading effects in the forests of Northern Europe, and that they are triggered by both direct and non‐lethal effects of predation.

Muutokset suurpetojen runsaudessa ovat aiheuttaneet huomattavia heijastevaikutuksia ekosysteemeissä eri puolilla maailmaa. Tässä väitöskirjassa tarkastelin useita mahdollisia ravintoverkkojen sisäisiä kaskadivaikutuksia sekä lajienvälisiä vuorovaikutussuhteita pohjoisella havumetsävyöhykkeellä. Työni päätavoitteena oli tutkia, onko pohjoisten havumetsien pedoilla suoria tai epäsuoria heijastevaikutuksia ravintoverkon alemmille trofiatasoille. Ensiksi vertasin aitauskokeissa eri nisäkäs‐kasvinsyöjien laidunnusvaikutuksia puiden taimiin siten, että estin myyrien, jänisten tai hirvieläinten pääsyn syömään rauduskoivuja (Betula pendula), mäntyjä (Pinus sylvestris) sekä kuusia (Picea abies). Lisäksi tutkin simuloidun saalistusuhkan vaikutusta myyrien laidunnukseen pöllöjen ääntelyä käyttämällä. Seuraavaksi selvitin ylemmillä trofiatasoilla petokillan sisäisiä vuorovaikutussuhteita käyttäen tutkimuslajeina maakotkaa (Aquila chrysaetos) sekä tämän saaliiksi toisinaan joutuvia kettua (Vulpes vulpes) ja näätää (Martes martes). Tutkiakseni kokonaista trofiakaskadia, selvitin lisäksi maakotkan ja mainittujen pienpetojen yhteisvaikutuksia teeren (Tetrao tetrix) sekä pyyn (Tetrastes bonasia) populaatioihin. Ennusteena oli, että kotkan läsnäolo voisi hyödyttää näitä metsäkanalintuja. Tutkituista puulajeista koivu vaikutti olevan alttein nisäkäskasvinsyöjien laidunnukselle. Havaitsin, että hirvieläinten läsnä ollessa koivujen kasvunopeus hidastui, kun taas jänikset ja myyrät alensivat näiden taimien selviytymistä. Tämän perusteella kaikki kolme nisäkäsryhmää heikentävät uusiutumista koivutaimikoissa. Lisäksi havaitsin, että simuloitu pöllön saalistusuhka vaikutti vähentävän koivujen laidunnuspainetta loppukesästä, vaikka tuolloin myyrien suosima ruoho on vanhaa ja vähemmän maittavaa. Myyrien ja jänisten laidunnuksella oli haitallinen vaikutus männyntaimien kasvuun ja kuntoon, mutta sen sijaan kuusentaimiin eivät nisäkäskasvinsyöjät juurikaan vaikuttaneet, ainakaan oloissa joissa vaihtoehtoista ravintoa on myös saatavilla. Havaitsin että maakotkan läsnäolo vähensi teeren runsautta, mutta toisaalta lisäsi poikasten osuutta sekä teeren että pyyn populaatioissa. Tämä maakotkan suotuisa suojeluvaikutus ei kuitenkaan ollut riippuvainen ketun tai näädän runsaudesta, eikä maakotka vähentänyt näiden pienpetojen lukumääriä. Sen sijaan kanalintuihin ulottuva suojeluvaikutus voi johtua kotkan aiheuttamasta pelotteesta ja sen välittäjänä voivat toimia myös muut pienpedot. Tämän väitöskirjan tulokset tarjoavat uutta, tärkeää tietoa pohjoisen havumetsävyöhykkeen ravintoverkoista. Ne korostavat sitä, miten eri nisäkäskasvinsyöjillä voi olla vaihtelevia vaikutuksia eri puulajien kasvuun ja kuntoon. Hirvieläinten vähentyminen voisi parantaa koivikoiden uudistumista, mikä epäsuorasti tukee ajatusta siitä, että hirvieläinten tärkeimmät pedot voisivat runsastuessaan aiheuttaa heijastevaikutuksia myös Fennoskandian metsissä. Pöllöt näyttävät vähentävän myyrien laidunnusta pelotevaikutuksen kautta, mikä on uusi löydös pöllöjen ääntelyn kaskadivaikutuksista, jota voidaan jopa soveltaa koivutaimikoiden suojaamisessa. Tarkastellessani väitöskirjani kolmatta trofiakaskadia havaitsin, että maakotkalla on suojeluvaikutus metsäkanalintuihin, joskin epäselväksi jää, minkä petolajien kautta tämä vaikutus välittyy. Kaiken kaikkiaan tämän väitöskirjan tulokset antavat lisää tukea ajatukselle, että Pohjois‐Euroopan metsissä esiintyy trofiakaskadeja, ja että ne lähtevät liikkeelle sekä petojen suorista saalistusvaikutuksista että epäsuorista pelotevaikutuksista.